The Influence of The Arabic Curriculum on Students’ Motivation and Perception in English Learning - Abdul Rahman Dzulhijah Sofyan; Agus Setiawan; Nurteteng (TEKILA: Journal of Language Teaching and Literature, 2025)
This study investigates the influence of an Arabic-oriented curriculum on students’ motivation and perceptions in learning English at a modern Islamic boarding school. English learning in multilingual educational contexts often presents unique challenges, particularly when another foreign language dominates daily instruction. This research aims to explore how the Arabic curriculum shapes students’ motivation and perceptions toward English learning. A qualitative case study design was employed. The participants were ten male students of Grade 3 TMI at Al-Ghuroba Modern Islamic Boarding School. Data were collected through questionnaires, in-depth interviews, and documentation. The questionnaire was used to identify students’ levels of motivation, while interviews explored students’ perceptions and learning experiences. The data were analyzed using descriptive qualitative analysis and thematic analysis to identify recurring patterns and meanings. The findings reveal that most students demonstrate moderate to high motivation in learning English, particularly when learning activities involve vocabulary practice and game-based tasks. These activities make English learning more enjoyable and meaningful for students. However, students still experience difficulties in grammar, translation, and sentence construction. Students’ perceptions of the influence of Arabic on English learning vary, indicating that multilingual exposure affects learners differently. Despite these challenges, students generally perceive English as useful for school activities and future opportunities. This study suggests that maintaining interactive learning strategies and providing clearer guidance in challenging areas can enhance English learning in Arabic-oriented educational settings